Potential of Liquid Smoke in Inhibiting the Growth of Pathogenic Bacteria: A Mini Review - Khusnul Azizah; Winda Shari; Charles Banon; Avidlyandi Avidlyandi; Khafit Wiradimafan; Salprima Yudha S.; Morina Adfa (Jurnal Biosilampari : Jurnal Biologi, 2025)
The objective of this study was to perform a comprehensive evaluation of the application of liquid smoke as a possible antibacterial agent. The studies were identified by conducting searches on multiple electronic databases, specifically Semantic Scholar, PubMed, and Google Scholar, from 2013 to 2024. The keywords used included ‘antibacterial of wood vinegar, antibacterial of pyroligneous extract, antibacterial of pyroligneous acid, antibacterial of wood distillate, antibacterial activity of liquid smoke, and aktivitas antibakteri asap cair (in Bahasa Indonesia)’. The results indicate that liquid smoke has the capacity to serve as a natural antibacterial agent against both Gram positive and Gram-negative microorganisms. The variation in antibacterial susceptibility may arise from the composition of chemical compounds present in liquid smoke, the raw materials employed in its production, the temperature of pyrolysis, and the specific testing methodology employed. This review will be useful to the industrial and scientific communities in the food science, pharmaceutical, and technology fields.